2011
DOI: 10.1186/1477-7525-9-35
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and short-term physical and cognitive dependence in critically ill persons 75 years and older: a prospective cohort study

Abstract: BackgroundThe purpose of this study was to identify predictors of 3-month mortality in critically ill older persons under medical care and to assess the clinical impact of an ICU stay on physical and cognitive dependence and subjective health status in survivors.MethodsWe conducted a prospective observational cohort study including all older persons 75 years and older consecutively admitted into ICU during a one-year period, except those admitted after cardiac arrest, All patients were followed for 3 months or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
3
39
2
Order By: Relevance
“…In this preliminary study, cognitive impairment and especially ADL impairment were positively correlated with the death risk. This is in accordance to several prospective studies which have confirmed that low educated patients who live alone or in long term institutions are most prone to have cognitive and ADL impairment leading to impending death 21 . Furthermore, patients with clinical diseases such as diabetes or hypertension tend to have more cognitive impairment than those without any disease, and also they have higher mortality rates [22][23][24][25] .…”
Section: Discussionsupporting
confidence: 75%
“…In this preliminary study, cognitive impairment and especially ADL impairment were positively correlated with the death risk. This is in accordance to several prospective studies which have confirmed that low educated patients who live alone or in long term institutions are most prone to have cognitive and ADL impairment leading to impending death 21 . Furthermore, patients with clinical diseases such as diabetes or hypertension tend to have more cognitive impairment than those without any disease, and also they have higher mortality rates [22][23][24][25] .…”
Section: Discussionsupporting
confidence: 75%
“…Jeitziner et al [20] reported that among older adults surviving ICU admission, a decline in physical functional status (measured by ADLs) was observed, and patients were likely to require assistance in perform such tasks as using public transportation, shopping, and doing laundry. Moreover, ICU survivors have documented worsening cognitive functions which could also explain the need for extended care at hospital discharge [21].…”
Section: Discussionmentioning
confidence: 99%
“…We also reviewed the bibliographies of relevant citations to identify additional citations. Overall, 19 studies met these criteria (2, 3, 2945): 17 studies reported disability outcomes (2, 2938, 4042, 44), 2 studies reported cognitive outcomes (3, 45) and 2 studies reported both (39, 43). …”
Section: Epidemiology Of Disability Following Critical Illnessmentioning
confidence: 99%
“…New or worsened IADL disability was also common and reported in 22% to 45% of patients evaluated 3 months to almost 2 years following the index illness (34, 38, 43). A single study where a number of patients were disabled in ADLs and IADLs at baseline (43% and 60%, respectively) reported no change in disability at 3-month follow-up (42). Finally, disability in mobility activities was present in 14% to 87% of patients assessed during the first year following their index illness.…”
Section: Epidemiology Of Disability Following Critical Illnessmentioning
confidence: 99%